(untitled) (Conferencea, 2024)
This article examines nonlinear thinking as one of the components of the cognition process. Particular attention is paid to the multivariate direction of thinking and the impossibility of adequately reflecting the nature of the system in knowledge by a single strict system of axioms and laws. The role of bifurcation and chaos in the implementation of nonlinearity and their impact on the stability of the system is also discussed. The importance of random influences on the system and their influence on probabilistic thinking of nonlinear thinking is also emphasized.